A Systematic Literature Review Bending Failure In Cold-Formed Steel Beam - Fauzi, Nur Alia Ahmad (Universiti Sains Malaysia, 2022)
Bending failures in cold-formed (CFS) steel beams refer to failures that occur in the steel section of a CFS beam when it is bent. Cold-formed steel (CFS) beams subjected to various bending scenarios should be able to handle various buckling modes. The systematic literature review from thirty-five papers are used to assess bending failure in cold-formed steel beams. The purpose of this study is to provide a systematic review of the literature on the effect of bending on the failure mode of cold-formed steel (CFS) sections, as well as the method of conducting the study, which can be experimental or numerical. When CFS is bent, the most common modes of failure are local buckling, global buckling, lateral-torsional buckling, and distortional buckling. The failure mode of bending in a CFS beam and the parameters that affected the failure mode of CFS beam in bending have been studied. The parameter affected the failure mode such as section properties, section geometries, additional materials, strength, elasticity, loading, and specimen resistance factor are found. However, the method used to investigate the bending failure in the CFS beam also has been investigated. This study concluded that the four-point bending test and the finite element (FE) method are the most commonly used experimental and numerical methods, respectively.